Sustainable supply chains – a framework for best practice assessment: results of the pilot study, BestLog project. - Piotrowicz, W; Cuthbertson, R; Islei, G (http://www.worldses.org/wseas.htm, 2007)
This paper presents results of a pilot study completed as part of the BestLog (Best Practices in Logistics) project. BestLog (www.bestlog.org) is a research project initiated by the European Commission (EC) and financed from the 6th Framework Programme. One of the project goals is to identify and promote best sustainable practices in logistics and supply chain management. This paper focuses on the development of a framework for assessment. The research methodology is presented first, followed by an overview of the collected cases. The overview includes information related to best practice characteristics, such as: industry and sector, supply chain area and relationships, country coverage and contextual aspects. The next section reviews EC policies on sustainability in transport and logistics. The main part of the analysis concentrates on the metrics and benefits reported in the case studies. Identified benefits are listed and compared with the EC policies as well as existing literature related to performance measurement and supply chains benchmarking. To reflect the requirement for a sustainable supply chain, the proposed framework is composed of three dimensions: economic, social and environmental. Each dimension is further subdivided into categories of metrics that could be used to assess the supply chain performance. These metrics represent a mixture of both hard (quantitative) and soft (qualitative) measures. Hard metrics such as costs, utilisation or number of accidents are relatively easy to measure, while the soft metrics will require judgment to determine their relative value. The case study analysis confirmed the domination of purely economic benefits - while social and environmental aspects are often ignored. The final part of the paper provides a working version of the framework for best practice assessment, as well as conclusions and recommendations for future research. Results of the analysis are being employed in field work (based on the multi-case study design), running simultaneously in 9 European countries.